When good luck turns against you: evidence on performance responses to noisy feedback - Arrigo, M.; Gomez-Gonzalez, C.; Lang, M. (Current Issues in Sport Science, 2026)
Providing and receiving feedback is a common practice. Yet, feedback has been shown to both enhance and, at times, impair subsequent performance (Kluger & DeNisi, 1996). A commonly overlooked aspect is that performance depends not only on ability but also on uncontrollable factors, commonly referred to as luck. When evaluations fail to disentangle the two, feedback can become over- or under-rewarding. This also affects result interpretation, since individuals typically credit themselves for success but blame bad luck for failure—a phenomenon known as the self-attribution bias (Miller & Ross, 1975). Despite its relevance, empirical evidence on how reactions to luck-distorted feedback affect subsequent performance remains scarce, largely due to difficulties in measuring true performance and noisy feedback in real-incentive settings.